PENGARUH GAYA KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA PADA PEGAWAI HOTEL JIMBARWANA JEMBRANA BALI - Anak Agung Ngurah Gede Suindrawan; Anak Agung Bagus Wirateja; Rahmat Hidayat; Anak Agung Ngurah Agung Redioka (Journal of Tourism and Interdiciplinary Studies, 2023)
This study aims to determine the effect of leadership style and communication on employee performance through employee work motivation in the employees of Jimbarwarna Hotel, located in Jembrana, Bali. The research sample consists of all employees, who serve as primary data sources. Data collection involves distributing questionnaires to all employees and conducting direct observations at the research site to gather additional necessary data.The collected data is then subjected to tabulation and undergoes various tests and analyses. These include validity tests, reliability tests, classical assumption tests (such as multicollinearity tests, heteroscedasticity tests, normality tests, and linearity tests), simple regression analysis, hypothesis testing using path analysis, and the Sobel test.The analysis conducted reveals that leadership style, through work motivation, has a positive and significant effect on employee performance. Similarly, communication, through work motivation, also has a positive and significant effect on employee performance. Additionally, work motivation itself has a positive and significant effect on employee performance.